Qualitative Insights Into Non-attendance for Scheduled Radiology Appointments at a Specialist Hospital in Saudi Arabia - Mooney, Mary; Corry, Margarita; Mc Kee, Gabrielle (My University, 2025)
Background: Patient non-attendance at radiology appointments is an international problem with significant implications for healthcare recipients and healthcare efficiency. Non-attendance impacts patient health, waiting lists, and other hospital departments, while increasing staff stress, anxiety, and fatigue. Understanding the reasons behind patient non-attendance is crucial for developing effective strategies to help improve attendance rates. Objective: This study explored the reasons for patient non-attendance at scheduled radiology appointments and identified potential strategies to enhance attendance at a Specialist Hospital in Saudi Arabia. Methods: Using semi-structured interviews, 9 men and 8 women who were purposively sampled and had missed scheduled radiology appointments at the research site were interviewed. Thematic analysis was employed to identify the key themes represented by the data. Findings: This qualitative study revealed the multifaceted nature of patient non- attendance at scheduled radiology appointments at the Specialist Hospital in Saudi Arabia. Five themes underlying non-attendance were identified. First, scheduling conflicts were a significant barrier. Second, a lack of adequate knowledge about health conditions was evident. Third, physician–patient miscommunication was a critical issue. Fourth, transportation difficulties, especially for those living far from the hospital or without personal transportation, were a key factor in non-attendance. Finally, personal reasons, such as fear of medical procedures and the patient’s health status, also contributed. The study identified two main areas for improvement: implementing an effective appointment reminder system and enhancing the radiology department by extending hours and addressing non-attendance more effectively. These strategies underscore the need for a patient-centred approach to reduce barriers to attendance. Conclusion: The findings suggest that patient non-attendance is multifactorial, involving personal and hospital-specific reasons. Strategies to improve attendance should thus be multifaceted, including better scheduling systems, enhanced patient education and communication, and reminder systems. These insights can inform targeted interventions to reduce non-attendance rates, ultimately improving healthcare delivery and resource utilisation.
PUBLISHED
DOI: 10.7759/cureus.79700
Keywords: patient non-attendance, radiology appointments, qualitative research, thematic analysis; Inclusive Society; Telecommunications; Health attitudes and behaviour; Health outcomes; Nursing; Public health; Other; Community; Health